Cultural Adaptation of the Modified Version of the Conflicts Tactics Scale (M-CTS) in Mexican Adolescents - Ronzón-Tirado, Rosa Carolina; Muñoz-Rivas, Marina Julia; Zamarrón Cassinello, María Dolores; Redondo Rodríguez, Natalia (Frontiers in Psychology, 2019)
Several scales are used in Dating Violence studies assuming cross-cultural invariance and equivalence of the measures without making the proper validation in the intended populations. This study focuses on the importance of adapting existing dating violence psychological instruments (as the widely recognized Modified Version of the Conflict Tactics Scale, M-CTS) in diverse adolescent populations adjusting to international validation procedures that ensure the cultural fit of the instrument and the measurement invariance of the construct. We sought to adapt the M-CTS in Mexican adolescents (N = 1861; 57.5% woman) following the ITC Guidelines for Translating and Adapting Test. We made an analysis of the linguistic and cultural variables, followed by a Confirmatory Factor Analysis, and the evaluation of Construct and Predictive Validities. We culturally modified six items and verified the four-factorial structure of the questionnaire proposed in previous studies (argumentation, psychological aggression, mild physical aggression and sever physical aggression). We also found significant correlations in between the scores of the M-CTS and the Aggression Questionnaire (AQ) and the Dominating and Jealous Tactics Scale (DJTS), verifying the Construct Validity of the M-CTS to measure aggressive behaviors. Conclusion: the cultural adaptation of the M-CTS offered adequate reliability and validity scores in Mexican population expanding the possibilities of comparing prevalences of the problem between nations with a reliable instrument based on the same theoretical and methodological perspectives.